Distal radial approach versus conventional radial approach: a comparative study of feasibility and safety. Issue 1 (1st January 2021) - Hammami, Rania; Zouari, Fatma; Ben Abdessalem, Mohamed Aymen; Sassi, Awatef; Ellouze, Tarek; Bahloul, Amine; Mallek, Souad; Triki, Faten; Mahdhaoui, Abdallah; Jeridi, Gouider; Abid, Leila; Charfeddine, Selma; et al.
ABSTRACT: The distal radial approach (DRA) is suggested to have benefits over the conventional radial approach (CRA) in terms of local complications and comfort of both patient and operator. Therefore, we aimed to compare the feasibility and safety of DRA and CRA in a real life population. We conducted a prospective, observational multicentric trial, including all patients undergoing coronary procedures in September 2019. Patients with impalpable proximal or distal radial pulse were excluded. Thus, the choice of the approach is left to the operator discretion. The primary endpoints were cannulation failure and procedure failure. The secondary endpoints were time of puncture, local complications and radial occlusion assessed by Doppler performed one day after the procedure. We enrolled 177 patients divided into two groups: CRA (n = 95) and DRA (n = 82). Percutaneous intervention was achieved in 37% in CRA group and 34% in DRA group (p = 0.7). Cannulation time was not significantly different between the two sets (p = 0.16). Cannulation failure was significantly higher in DRA group (4.8% vs 2%, p < 0.0008). Successful catheterization was achieved in 98% for the CRA group and in 88% for the DRA group (p = 0.008). Radial artery occlusion, detected by ultrasonography, was found in 3 patients in the CRA group (3.1%) and nobody in the DRA group (p = 0.25). The median diameter of the radial artery diameter was higher in the DRA than the CRA group (2.2 mm vs 2.1 mm; p = 0.007). The distal radial approach is feasible and safe for coronary angiography and interventions, but needs a learning curve.